2003
DOI: 10.4049/jimmunol.170.9.4612
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Regulates Lymphocyte Homeostasis by Preventing Activation and Subsequent Apoptosis of Peripheral Lymphocytes

Abstract: TGF-β1 plays an important role in the maintenance of immune homeostasis and self-tolerance. To determine the mechanism by which TGF-β1 prevents autoimmunity we have analyzed T cell activation in splenic lymphocytes from TGF-β1-deficient mice. Here we demonstrate that unlike wild-type splenic lymphocytes, those from Tgfb1−/− mice are hyporesponsive to receptor-mediated mitogenic stimulation, as evidenced by diminished proliferation and reduced IL-2 production. However, they have elevated levels of IFN-γ and eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 71 publications
4
67
0
1
Order By: Relevance
“…26 TCR␣␤ and CD4 ϩ T lymphocytes were present in similar proportions in our 6-week-continuous and discontinuous animals; however, their significantly smaller size in the continuous mice suggested that they were less activated than in acute or discontinuous animals. 27,28 T-cell activation in continuous mice may have been suppressed by the local production of anti-inflammatory cytokines, such as TGF-␤ and IL-10. Airway TGF-␤ levels increased during the 10-day-acute OVA aerosol period and again during the acute OVA re-exposure in 6-weekdiscontinuous animals, possibly as part of a homeostatic mechanism that limits airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…26 TCR␣␤ and CD4 ϩ T lymphocytes were present in similar proportions in our 6-week-continuous and discontinuous animals; however, their significantly smaller size in the continuous mice suggested that they were less activated than in acute or discontinuous animals. 27,28 T-cell activation in continuous mice may have been suppressed by the local production of anti-inflammatory cytokines, such as TGF-␤ and IL-10. Airway TGF-␤ levels increased during the 10-day-acute OVA aerosol period and again during the acute OVA re-exposure in 6-weekdiscontinuous animals, possibly as part of a homeostatic mechanism that limits airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with recent observations that TGFβ1 and IL-6 are essential for T h 17-cell differentiation, T h 17 cells are absent in Tgfb1 −/− mice, suggesting that Tgfb1 −/− T cells cause autoimmune disease without differentiating into T h 17 cells [19,34]. Because Tgfb1 −/− T cells produce interferon (IFN)-γ but not IL-17, it is possible that IFN-γ produced by T h 1 cells inhibits T h 17-cell development [22,34,35]. Tgfb1 −/− T cells do differentiate into T h 17 cells in vitro in the presence of added TGFβ1 and anti-CD3, suggesting that the lack of T h 17-cell development in Tgfb1 −/− mice is owing to the presence of abundant IFN-γ, the absence of TGFβ1 or both.…”
Section: Phenotypes Of Tgfβ1-deficient Micementioning
confidence: 99%
“…In T cells, TGFβ1 also signals through a Caenorhabditis elegans Sma and Drosophila Mad proteins (SMAD)-independent Ca 2+ -calcineurin-nuclear factor of activated T cells (NF-AT) cascade that inhibits naïve T-cell activation [21,22]. Lack of TGFβ ligand-binding might prevent translocation of FK506 binding protein 12 (FKBP12) from the TGFβ1-receptor complex to a ternary complex with the IP 3 receptor and calcineurin, where it prevents Ca 2+ channels from leaking [23].…”
Section: Tgfβ1 Signaling In T Cellsmentioning
confidence: 99%
“…7 Culture supernatants were collected and frozen until cytokines were analyzed by sandwich ELISA as described earlier. 7 Phenotype analysis of splenocytes was determined by four-color flow cytometry using BD-LSR flow cytometer with the appropriate fluorochrome-conjugated antibodies (BD Pharmingen, San Diego, CA, USA) as described. 7 Cells were stained for surface markers, as described previously.…”
Section: Pcr Genotypingmentioning
confidence: 99%
“…4 Consequently, TGFβ1 plays an intrinsic role in preventing T-cell activation and activation-induced cell death. [5][6][7] We have previously shown that Tgfb1 −/− T cells are activated in vivo due to a lowered threshold of activation resulting from increased [Ca 2+ ] i levels. 8 Unlike TGFβ1 function in T reg cells which is SMAD3 dependent, 9,10 Ca 2+ /Calcineurin-mediated TGFβ1 function in T cells is SMAD3 independent since Smad3 −/− mice do not have this autoimmune disease.…”
mentioning
confidence: 99%